2003
DOI: 10.1017/s1366728903001007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bilingualism on theory of mind development

Abstract: This research examines whether an individual's linguistic knowledge, either as a speaker of a particular language or as a bilingual, influences theory of mind development. Three-and four-year-old English monolinguals, Mandarin Chinese monolinguals, and Mandarin-English bilinguals were given appearance-reality, level 2 perspective-taking, and false-belief tasks. All children were tested twice, a week apart; the bilinguals were tested in each of their languages. The 4-year-olds in each group performed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
254
5
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(272 citation statements)
references
References 41 publications
9
254
5
4
Order By: Relevance
“…Theory of Mind studies have revealed that 3-year-old bilinguals outperform monolingual children of the same age in standard FB tasks (Goetz, 2003;Berguno & Bowler, 2004;Kovács, 2009Kovács, , 2012Nguyen & Astington, 2014;Gordon, 2016; see also Bialystok & Senman, 2004;Greenberg et al, 2013), and parallel results have been reported with bilingual adults (Rubio-Fernández & Glucksberg, 2012). These studies discuss a number of experiential factors that could boost bilinguals' understanding of false belief, such as having greater metalinguistic awareness (e.g.…”
Section: Bilinguals Outperform Monolinguals In Fb Tasksmentioning
confidence: 64%
See 2 more Smart Citations
“…Theory of Mind studies have revealed that 3-year-old bilinguals outperform monolingual children of the same age in standard FB tasks (Goetz, 2003;Berguno & Bowler, 2004;Kovács, 2009Kovács, , 2012Nguyen & Astington, 2014;Gordon, 2016; see also Bialystok & Senman, 2004;Greenberg et al, 2013), and parallel results have been reported with bilingual adults (Rubio-Fernández & Glucksberg, 2012). These studies discuss a number of experiential factors that could boost bilinguals' understanding of false belief, such as having greater metalinguistic awareness (e.g.…”
Section: Bilinguals Outperform Monolinguals In Fb Tasksmentioning
confidence: 64%
“…Since most of the Theory of Mind studies that compared bilingual and monolingual children used standard FB tasks (Goetz, 2003;Berguno & Bowler, 2004;Kovács, 2009;Nguyen & Astington, 2014, Gordon, 2016; but cf. Bialystok & Senman, 2004;Kovács, 2012), the bilingual children in these studies may not have necessarily shown better inhibition of the dominant TB response, as is generally assumed.…”
Section: Why Do Bilingual Children Perform Better In Fb Tasks?mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to monocultural children, bicultural children have been reported to show an advanced, equal, and delayed development of ToM. For example, by only analyzing the data of bicultural children whose verbal scores were above 64, the lowest score that the monocultural children in her study received on the Peabody Picture Vocabulary Test (PPVT), Goetz (2003) found that Chinese American 3-and 4-year-olds outperformed European-American and mainland Chinese children on ToM tasks. Similarly, Bialystok and Senman (2004) used language proficiency as a covariant in their analysis and found that compared to Canadian monolingual children, bilingual 4-and 5-year-olds developed ToM faster.…”
Section: The Development Of Theory Of Mind In Bicultural Childrenmentioning
confidence: 99%
“…Hence, it is important to study the development of ToM in preschoolers in particular. However, compared to research on monocultural children, relatively few studies have been conducted on the development of ToM in bicultural preschoolers (Bialystok & Senman, 2004;Doan & Wang, 2010;Goetz, 2003;Liu, Wellman, Tardif, & Sabbagh, 2008;Vinden, 2001;Wang, Hutt, Kulkofsky, McDermott, & Wei, 2006). Therefore, the current study aimed to expand this area of research by examining ToM among English-speaking Chinese preschoolers in Singapore.…”
mentioning
confidence: 99%